AN ASSEMENT OF THEMATIC OPTIMISM IN THE NOVELS OF MULK RAJ ANAND - ANURAG JADAUN, M.A., M.Phil. (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Mulk Raj Anand, one of the pioneer authors of Indian Writing in English, highlights the problems of underprivileged and the poor of Indian social system. He presents a plethora of images which are realistic representation of the condition of the downtrodden. His characters are usually trapped between the poverty and atrocities of the dominant class. He exposes the faults of decomposing contemporary Indian social system and ultimately gives hopefulness that one day social amelioration will take place. Despite of gloomy atmosphere of his novels due to the exposition of problems of the poor, the theme of his novels offersa vibrant optimism for the future.